Greenhouse gas emissions balance estimate of the chaco sustentable project, Paraguay initiative on climate and agriculture value chain - Costa Junior, Ciniro (Fundación Solidaridad, 2022)
This study presents the greenhouse gas (GHG) emissions estimates calculated during the implementation of the Chaco Sustentable Project, led by Solidaridad in the Chaco region. The project consists of farmer capacity building on sustainable intensification of dairy production based on the progressive recovery of degraded pasturelands and adoption of integrated farm management. By 2027, the Project has the average potential for reducing GHG emissions in farms taking part in the Chaco Sustentable Project of 92% per hectare and 97% perliter of milk produced, with a 33% increase in milk productivity compared with the begin-ning of the program. In year one, the project already achieved an increase of almost 17% in milk productivity and has reduced GHG emissions by 29% per hectare of pasture and by 63% per liter of milk produced. These results were achieved by a strategy designed to recover about 4 ha of the pasture area using fencing and planting Algarrobo trees on the farms taking part in the project initially. Those recovered areas represent from 1 to 17% of the pasture of the farm types covered by the program. Additionally, this strategy introduces and improves practices such as rotational grazing, animal supplementation (sorghum silage), health and breeding techniques, and management systems to ensure the sustainability of the farms as a whole. The assessment carried out shows that the strategy adopted by the Chaco Sustentable Project has reduced GHG emission levels of the participating farms to levels similar to the best levels recorded worldwide which, if scaled up these practices, could contribute close to 4% of the entire Paraguay commitment to the Paris Agreement. This paper also shows the potential and capacity of dairy farming in the Paraguayan Chaco region to reduce its GHG emis-sions and increase production. At the same time, it can also help decision-makers, consumers, and other actors in the Dairy and Meat value chain to realize the import-ant role played by large-scale sustainable production in preventing climate change and meeting food demands.